Study of concrete containing washed copper slag - Ong, Boon Seng. (2009)
Copper slag is a by-product obtained during the matte smelting and refining of copper. Production of one ton of copper generates, approximately 2.2–3 tons copper slag. In the United States, the amount of copper slag produced is about four million tons, and in Japan, it is about two million tons per year Current options for management of copper slag include recycling, recovering of metal, production of value added products and disposal in slag dumps or stockpiles. Currently, copper slag has been widely used for abrasive tools, roofing granules, cutting tools, abrasive, tiles, glass, road-base construction, railroad ballast, asphalt pavements, cement and concrete industries. Another option of reusing copper slag is by using it as a partial replacement of concrete, it will be possible to reuse a waste by-product material beneficially. Large amounts of copper slag can be utilized by using it as fine and coarse aggregates in concrete because more than 75% volume of concrete is occupied by aggregates. The use of copper slag in cement and concrete provides potential environmental as well as economic benefits for all related industries, particularly in areas where a considerable amount of copper slag is produced.